1995
DOI: 10.1093/clinids/21.5.1159
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Colitis and Hepatitis Due to Previously Uncharacterized Spirochetes in Patients with Advanced Human Immunodeficiency Virus Infection

Abstract: We describe three patients with advanced human immunodeficiency virus (HIV) infection, two with colitis and one with cholestatic hepatitis, for whom results of detailed endoscopic and histologic studies were suggestive of invasive spirochetosis. In the two patients with colitis, colonoscopic evaluation revealed either diffuse ulcerations or pustules; in both cases, there was histologic evidence of extensive superficial cell necrosis and infiltration of the mucosa and lamina propria with acute inflammatory cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 22 publications
2
48
0
1
Order By: Relevance
“…In certain immunocompromised or debilitated humans, spirochaetes resembling S . pilosicoli have been isolated from regions of the body beyond the large intestine, including the liver (Kostman et al, 1995), and S. pilosicoli has been isolated from the bloodstream (Fournik-Amazouz et al, 1995 ;Trott et al, 1997a). S .…”
Section: Introductionmentioning
confidence: 99%
“…In certain immunocompromised or debilitated humans, spirochaetes resembling S . pilosicoli have been isolated from regions of the body beyond the large intestine, including the liver (Kostman et al, 1995), and S. pilosicoli has been isolated from the bloodstream (Fournik-Amazouz et al, 1995 ;Trott et al, 1997a). S .…”
Section: Introductionmentioning
confidence: 99%
“…In humans, B. pilosicoli is one cause of intestinal spirochetosis, a condition characterized by end-on attachment of the organism to colorectal epithelial cells (9,16,21). In several reports, intestinal spirochetosis was the only abnormal finding for patients with abdominal pain, rectal bleeding, and diarrhea, and many of these symptoms were long-term or recurrent (4,12,16).B. pilosicoli has been isolated at a prevalence of 10 to 30% from the feces of a range of different human population groups, including Aboriginal Australians (3, 15), individuals from developing countries (2, 3, 23), homosexual males, and human immunodeficiency virus-positive individuals (21).…”
mentioning
confidence: 99%
“…In humans, B. pilosicoli is one cause of intestinal spirochetosis, a condition characterized by end-on attachment of the organism to colorectal epithelial cells (9,16,21). In several reports, intestinal spirochetosis was the only abnormal finding for patients with abdominal pain, rectal bleeding, and diarrhea, and many of these symptoms were long-term or recurrent (4,12,16).…”
mentioning
confidence: 99%
“…In another study, spirochetal invasion was observed in two HIV ϩ patients where there was an extension of IS into the crypts of Lieberkühn, with spirochetal invasion of the colonic mucosa, and a marked inflammatory response that involved macrophages in the underlying lamina propria (127). Spirochetes that are presumed to have been B. pilosicoli also have been observed in the livers of immunocompromised human patients who had invasive colitis (128). There also has been a report of aborted fetuses from young women showing nontreponemal spirochetes in the lumen and mucosa of the intestine, as well as, less commonly, in other organs (129).…”
Section: Observations In Natural and Experimental Infectionsmentioning
confidence: 97%